Análise espacial de soro prevalência para Lyssavírus SPP em animais domésticos do Município de Curuçá-PA - ANJOS, Flaviane Márcia Lima dos (2024)
The present research aims to carry out a spatial analysis, characterizing demographic aspects of dogs and cats, which are prevalent sera for the rabies virus spp, in the municipality of Curuçá. This is research carried out in the second half of 2019, within the scope of the project Epidemiological Analysis of Rabies and attacks by vampire bats on humans and non-humans in the Amazon Region coordinated by professor Drª. Isis Abel, in which serology for Lyssavirus was carried out with serum samples from dogs and cats, domiciled in the municipality of Curuçá. Furthermore, the Municipal Mesh from the IBGE cartographic database was used to complement the analysis. A total of 300 animals were reached by proportional stratified random sampling. and spatialized in Qgis, highlighting areas with a higher incidence of infection. The highest incidence of rabies infection was in the center of the Municipality of Curuça, where the chances of animals becoming infected are greater than in the interior of the Municipality. Therefore, this article is expected to contribute to understanding the maintenance cycle of the rabies virus in certain geographic areas with the purpose of helping to develop strategies and measures to control and prevent the disease and its adverse effects on public health in the context local.